Financial frictions and inflation differentials in a monetary union - Nikolay Hristov; Oliver Hülsewig; Timo Wollmershäuser (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper employs a stylized New Keynesian DSGE model for a monetary union to analyze whether cyclical inflation differentials can be explained by cross-country differences concerning the characteristics of financial markets. Our results suggest that empirically plausible degrees of heterogeneity with respect to two important credit market characteristics - namely the fraction of borrowers and to a lesser extent the loan-to-value ratio - generate inflation differentials that are similar to those implied by structural differences with respect to price inertia and the degree of competitiveness. Hence, the characteristics of financial markets should be seen as a possible alternative explanation for the observable inflation dispersion in the EMU.
Keywords: E32; E44; E52; F41; G10; 330; monetary union; inflation; differentials; collateral constraints; cross-country heterogeneity; household indebtedness; Währungsunion; Inflation; Finanzmarkt; Marktstruktur; Kreditsicherung; Verschuldungsrestriktion; Theorie